An innovative user-centred support tool for Augmented Reality maintenance systems design: a preliminary study - Fernández del Amo, Iñigo; Galeotti, Elisa; Palmarini, Riccardo; Dini, Gino; Erkoyuncu, John Ahmet; Roy, Rajkumar (Elsevier, 2018)
Augmented Reality (AR) technologies in maintenance are demonstrated to positively impact on technicians’ work and performance. Current research in this area is mainly focused on solving technical challenges related with AR in industrial environments. Limited attention has been put into the user perception, ergonomics and usability aspects of AR systems design. This paper proposes an innovative user-centred design support tool for AR systems in maintenance contexts. The tool is based on the Analytic Hierarchy Process (AHP), which is a well-established multi-criteria decision-making approach. In this research, AHP is utilised for guiding designers in the evaluation of application-contexts and AR-technologies for selecting the most suitable and effective AR interaction solution. The tool’s validation has been conducted with twelve maintenance-experts in a design workshop using two case studies. The quantitative results obtained in both case studies reveal the applicability of the AHP model, as well as the effectiveness of the design support tool for complex decisions in AR for maintenance. The use of AHP methods for AR design enable experts to deal with complex and contrasting concepts and express a preference among them with a subjective judgement based on their personal understanding of the problem. Therefore, simplifying the design of AR systems for complex maintenance contexts.
Keywords: Augmented Reality; Maintenance; Systems Design; Analytical Hierarchy Process